2020
DOI: 10.1002/jso.26186
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the relationship between hospital characteristics and survival in ovarian cancer: A historical cohort

Abstract: Background and Objectives: The management of ovarian cancer requires complex surgical and medical interventions. Specialized care is associated with superior outcomes in early and advanced stages. This study aimed to estimate the effect of hospital characteristics on the overall survival of women with epithelial ovarian cancer. Methods: We established a cohort with data recorded by the Fundação Oncocentro de São Paulo cancer registry. We included 6111 women treated for ovarian cancer in the state of Sao Paulo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…For this reason, patients who develop HSRs should be seen and tested within one to two weeks of the reaction. This underscores the importance of a multidisciplinary approach to gynecologic cancer care in specialized centers and adherence to clinical guidelines, which ensures a better prognosis and quality of life for patients [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In particular, it has been shown that the collaboration of different experts leads to an increased awareness of potential treatments and a better evaluation of diagnostic–therapeutic areas beyond their own competence, which ultimately improves the effectiveness of treatments [ 28 , 29 , 30 , 31 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, patients who develop HSRs should be seen and tested within one to two weeks of the reaction. This underscores the importance of a multidisciplinary approach to gynecologic cancer care in specialized centers and adherence to clinical guidelines, which ensures a better prognosis and quality of life for patients [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In particular, it has been shown that the collaboration of different experts leads to an increased awareness of potential treatments and a better evaluation of diagnostic–therapeutic areas beyond their own competence, which ultimately improves the effectiveness of treatments [ 28 , 29 , 30 , 31 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that ovarian cancer patients benefit from surgical treatment being performed in high-volume hospitals 19 . In São Paulo, ovarian cancer has demonstrated high rates of centralization 20 . Disruptions to healthcare services challenge this centralized model since patient treatment could be impacted if resources in a region become suddenly unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that ovarian cancer patients bene t from surgical treatment being performed in high-volume hospitals [23]. In Sao Paulo, ovarian cancer has demonstrated high rates of centralization, with a majority of patients included in the Hospital Cancer Registry being treated in high-volume hospitals [24]. Disruptions to healthcare services such as the COVID-19 pandemic challenge this centralized model.…”
Section: Discussionmentioning
confidence: 99%